Systematic clinical management of patients with candidemia improves survival. Issue 2 (August 2018) - Murri, Rita; Giovannenze, Francesca; Camici, Marta; Torelli, Riccardo; Ventura, Giulio; Scoppettuolo, Giancarlo; Sanguinetti, Maurizio; Cauda, Roberto; Fantoni, Massimo
Highlights: Candidemia is a high-mortality disease, keystone of antifungal stewardship programs. Clinical management includes both therapeutic and non-therapeutic aspects of care. A systematic clinical management is difficult to achieve in clinical practice. An appropriate and systematic clinical approach to candidemia improves survival. Summary: Objectives: Taking into account the significant morbidity, mortality, and hospital costs related to Candidemia, our objective is to define if improving appropriateness in candidemia management was associated with better clinical outcomes. Methods: A prospective observational monocentric cohort study was conducted. Adherence to five main elements was examined: appropriate selection of initial therapy; follow-up blood culture; echocardiography; ophthalmological examination; and removal of a central venous catheter. The correlation between the number of appropriate elements achieved and 30 day survival was examined. Results: Patients with candidemia ( n  = 213) were enrolled. Adherence to all five elements was achieved in 36 cases (16.9%), while the majority adhered to three or four elements (28.2% and 37.1%, respectively). Multivariable Cox regression analysis revealed that the number of elements achieved was associated with survival [HR: 0.39 (0.30–0.52); p < 0.001]. Also, the number of elements achieved correlated positively with duration of therapy ( p  = 0.01), but not length of hospital stay ( p  = 0.56). Conclusions: Five elements, including therapeutic and non-therapeutic-related aspects, of care were good indicators of appropriate management of patients with candidemia. Implementation of evidence-based practice regarding optimal clinical management is crucial for any antimicrobial stewardship program.